Analisis Pembelajaran Berdiferensiasi sebagai Strategi Inovatif dalam Meningkatkan Kualitas Pendidikan Siswa Sekolah Dasar - Sukma Arum Sari; Alya Yulieta; Nicky Tri Handayani (Jurnal Multidisiplin Ibrahimy)
Differentiated learning is a learning approach that recognizes that each student has different learning styles, interests and abilities. In the elementary school context, implementing differentiated learning can create a more inclusive and effective learning environment. This article will discuss the concept of differentiated learning in depth, including its basic principles, benefits for students, and challenges that teachers may face in implementing it. Differentiated Learning is a learning approach that recognizes that each student has different learning styles, interests and abilities. In this learning, teachers no longer teach all students in the same way, but rather adapt teaching to suit the individual needs of each student.Keywords: Differentiated learning, learning styles and interests.